Family Podospongiidae de Laubenfels, 1936. Pp. 694–702. In: Hooper, J.N.A. & Van Soest, R.W.M. (2002). Systema Porifera – A Guide to the Classification of Sponges (2 volumes).(Kluwer Academic/Plenum, New York, 1708 + xvliii. - Kelly, M.; Samaai, T. (2002)
Podospongiidae de Laubenfels (Demospongiae, Poecilosclerida) is resurrected to include taxa previously referred to Latrunculiidae Topsent based on the possession of spinose microrhabds (spinorhabds), as compared to acanthodiscorhabds, or ‘chessman’ spicules, in the latter. The family includes Podospongia, Sigmosceptrella, Diacarnus and Negombata, defined as having spinorhabds in one or two size classes disposed in a dense crust or scattered in a band within the ectosome. The family is included in Mycalina as incertae sedis based on an interpretation that the protorhabd of spinorhabds is sigmoid and potentially a sigmancistra derivative. The family also has clearly differentiated ectosomal and choanosomal skeletons; an extremely collagenous texture; where known, a viviparous reproductive strategy incubating large conspicuous bright yellow larvae; oxeas, strongyles, and variants of these megascleres; and a range of distinctive chemistries including norsesterterpene peroxides, to which cytotoxic latrunculins in Negombata are added, supporting postulated affinities with Mycalina and clearly differentiating them from Latrunculiidae. Species of Podospongiidae are more common in tropical and subtropical waters, occasionally also found in temperate and cold deep waters.
The PDF supplied here is a proof - NOT the definitive printed text - of a chapter of the Systema Porifera